Overweight and Obesity Conditions: Prevalence and Associated Risk Factors in Nursing Students in a Public University in Medellín, Colombia - Hugo Alberto Múnera Gaviria (Universidad de Antioquia, 2017)
Objective. This work sought to identify the prevalence of overweight and obesity conditions and the associated factors in nursing students in a public university in Medellín, Colombia.